YUNIS-VARON SYNDROME - Siddique, Abdul Wahab; Ahmed, Zeeshan; Haider, Ammar; Khalid, Hina; Karim, Tooba (Journal of Ayub Medical College Abbottabad, 2019)
Yunis-Varon syndrome is a rare autosomal recessive disorder with characteristic facial features and limb anomalies. We report a neonate born to consanguineously married normal parents with typical clinical and radiologic features of Yunis-Varon syndrome along with complete cleft lip and palate: an infrequent association. The family had two previous babies with similar features who died in infancy. This is a first reported case of Yunis-Varon syndrome in Pakistan. Keywords: Cleidocranial dysplasia; aplastic thumb and toes; Yunis-Varon syndrome